Mechanical properties of lightweight composite: polyurethane reinforced with kenaf core particles: article - Amarudin, Muhamad Akmal; Abu Bakar, Noor Fitrah (2017)
The objective of this paper was to study the effects of pulverized kenaf core particles on the mechanical properties (compressive and impact), density and as well as the pore size of polyurethane composite and to compare the compressive stress of the polyurethane with expanded polystyrene foam (EPS). The composite was prepared by mixing of polyols with different kenaf particle sizes such as <125 µm, 125-300 µm and >300 µm and for each different size of kenaf particles, different kenaf core particles loadings were also prepared; 5 wt%, 10 wt% and 15 wt% before mixing with diphenylmethane 4,4’-Diisocyanate . The samples were cut into standard samples shape for compressive and impact testing. The density and pore size of each sample was analyzed. Based on the result , the kenaf particles size of >300 µm at 15 wt% particles loadings exhibited the best compressive stress while for 10 wt% particle loading for all kenaf core particles size class, the compressive stress decreased. The additions of the kenaf core particles increased the pore size of the polyurethane hence make the decreased in the density. Moreover the polyurethane with >300 µm pulverized kenaf core particles sizes with 10 wt% and 15 wt% particles loadings possessed the highest impact strength while the impact strength decreased as the percent loadings increased for <125 µm kenaf core particles size. As conclusion, the expanded polystyrene foam (EPS) has lower density with higher compressive stress compared to polyurethane reinforced with kenaf core particles.